Salient man-made object detection based on saliency potential energy for unmanned aerial vehicles remote sensing image. Issue 14 (6th December 2019) - Cong, Ming; Han, Ling; Ding, Mingtao; Xu, Miaozhong; Tao, Yiting
Abstract: It is difficult to automatically recognize complex ground objects, and massive data images with the super-high ground resolution in images captured by unmanned aerial vehicles (UAVs). In order to directly identify the salient man-made ground objects from the UAV remote sensing (RS) image, a saliency detection method based on saliency potential energy (SPE) is proposed. With a detection, filtration and backtracking strategy, the texture, shape and colour of the UAV RS image are comprehensively and numerally analysed by the SPE to detect the salient man-made objects. Both qualitative and quantitative evaluations have indicated that, compared to the state-of-art saliency detection methods, our method could achieve better performance with better accuracy and less errors, which prove that our method has great application potential in UAV RS image understanding.